PENGARUH MANAJEMEN MODAL KERJA PADA PROFITABILITAS PERUSAHAAN MANUFAKTUR - Rustia Dewi, Ni Made; Supartha Wisadha, I Gede (E-Jurnal Akuntansi; Vol 12 No 3 (2015), 2015)
The purpose of this study is to examine the effect of working capital management on the profitability of manufacturing companies listed in Indonesia Stock Exchange in 2011-2013 period. The independent variables tested are average collection period (ACP), inventory turnover in days (ITID) and the average payment period (APP) while the dependent variable in this study is profitability that proxied by gross profit margin (GPM). These samples included 61 companies with nonprobability sampling method. Data were analyzed using multipe linear regression analysis technique. The result show that the average collection period (ACP) inventory tuenover in days (ITID), and the average payment period (APP) had a negative effect on profitability.
Keywords: ACP, ITID, APP, dan GPM